FINANCIAL FACILITIES AND SUSTAINABLE CHILD LABOUR PROGRAMMES IN GHANA - Kwofie, Samuel; Kessey, Kweku Dwomor; Dinye, Romanus (Advances in Social Sciences Research Journal, 2018)
Government of Ghana and other stakeholders have been putting up a lot of interventions to handle child labour related issues. Skill Development Training(s) have been provided the parents and guardians of these children. This study seeks to link up with the necessary financial institutions so that they could assist these vulnerable people to make the withdrawal process sustainable. This exercise used largely qualitative research method and marginally quantitative type. It was established that , there exist financial and micro- credit schemes within the country; poor arrangements of funding services to benefit the empowered family, high credit risk among empowered family. It was recommended that the micro financial institutions should define pro- poor products; implementing agencies should factor their training to include better skills development programmes that could help the target groups by making them attractive. It was concluded that to make the withdrawal process more formidable, there is the need to liaise with the funding agencies that can support these people.